All‐Solid‐State Batteries with a Limited Lithium Metal Anode at Room Temperature using a Garnet‐Based Electrolyte. Issue 1 (25th November 2020) - Chen, Shaojie; Zhang, Jingxuan; Nie, Lu; Hu, Xiangchen; Huang, Yuanqi; Yu, Yi; Liu, Wei
Abstract: Metallic lithium (Li), considered as the ultimate anode, is expected to promise high‐energy rechargeable batteries. However, owing to the continuous Li consumption during the repeated Li plating/stripping cycling, excess amount of the Li metal anode is commonly utilized in lithium‐metal batteries (LMBs), leading to reduced energy density and increased cost. Here, an all‐solid‐state lithium‐metal battery (ASSLMB) based on a garnet‐oxide solid electrolyte with an ultralow negative/positive electrode capacity ratio (N/P ratio) is reported. Compared with the counterpart using a liquid electrolyte at the same low N/P ratios, ASSLMBs show longer cycling life, which is attributed to the higher Coulombic efficiency maintained during cycling. The effect of the species of the interface layer on the cycling performance of ASSLMBs with low N/P ratio is also studied. Importantly, it is demonstrated that the ASSLMB using a limited Li metal anode paired with a LiFePO4 cathode (5.9 N/P ratio) delivers a stable long‐term cycling performance at room temperature. Furthermore, it is revealed that enhanced specific energies for ASSLMBs with low N/P ratios can be further achieved by the use of a high‐voltage or high mass‐loading cathode. This study sheds light on the practical high‐energy all‐solid‐state batteries under the constrained condition of a limited Li metal anode. Abstract : Owing to the stability between lithium metal and a garnet‐type solid electrolyte, all‐solid‐state lithium‐metal batteries (LMBs) are proved to possess longer cycling life than that of liquid‐state LMBs under limited lithium‐anode condition. Moreover, all‐solid‐state LMBs with long cycling life using a limited lithium‐metal anode are achieved at room temperature through a hybrid solid‐state electrolyte design.